TAHSIN DAN TAQBIH DALAM LEGISLASI HUKUM ISLAM DAN MAQASID AL-SHARIAH - Nurul Iman (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
The problem of al-hakim (law makers) or syari?ah is a contentious issues of Ushul Fiqh especially related to al-hakim or judge before the prophetic of Prophet Muhammad. This debate raise the concept of al-tahsin and at-taqbih. There were groups of Ahlu Sunna, Mu?tazilah, and Maturidiyah. This debate had an implication for the differences in: (a) the status of persons who had not reached him an Islamic dakwah or propaganda; (2) syukral mu?im (the obligation of grateful to the delights giver); and (c) the position of mind in ijtihad. This paper will elaborate these debates with the following appeared impacts.